Dressing attitudes of Obese female students aged 15-19 - Masukat, Yasmin Zorayda G.
This study is about how young women from ages 15-19, those considered obese, dress up. This study sought to answer the following questions: Are there physical and social aspects that prevent them from dressing up the way they want to? Are there any concerns that they have when choosing clothing for themselves? A survey conducted consisting of 40-50 respondents from selected secondary schools and colleges within the researcher's area namely St. Scholastica Marikina, St. Bridget School (Quezon City), University of the Philippines Integrated School (Quezon City), University of the Philippines: Diliman (Quezon City), Miriam College (Quezon City), OLPH School (Santolan, Pasig) and for the manila area, University of Sto. Tomas and Centro Escolar University (Manila). It is the main objective of this study to be able to evaluate the clothing attitudes of these female students. The descriptive research is utilized for this study. Specifically, descriptive method concerned with gathering of data about existing conditions. Books and journals were also used to support the results. The researcher used convenience sampling wherein the respondents were chosen according to availability. Questionnaire following the Likert Scale procedure with Strongly Agree, Agree, Uncertain, Strongly Disagree for the choices were employed. (see Methodology, p.29) Based from the responses of the 40 respondents, this study concluded that most of them have positive outlook towards clothing. The results obtained from both the positive and negative portion of the questionnaire showed the respondents positive attitude toward their being obese and dressing. The study found it unnecessary to make a dressing guide for the respondents. The positive attitude of the respondents made the study recommend the enhancement of self-esteem instead.